2018
DOI: 10.36803/2621-7678.07(2).01
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of VO2 max in Patient with Restrictive Pulmonary Disorder after Deep Breathing Exercise

Abstract: Introduction: Restrictive pulmonary disorder is reducing VO2 max values. It can be caused by lung can’t take oxygen from outside air freely. Pulmonary rehabilitation is known to increase the VO2 max. One of the pulmonary rehabilitation is deep breathing exercise. In this study aimed to know the improvement VO2 max after deep breathing exercise. Methods: This was an experimental without control pre and post-experimental study. The Six Minutes Walking Test (6MWT) was measured in patients with restrictive pulmona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The results revealed that there was a significant enhancement in oxygen saturation evaluated by pulse oximeter. Also, a study made by Destanta et al 52 to investigate the impact of diaphragmatic deep breathing exercise on oxygen saturation in active smokers. The exercise resulted in significant improvement in oxygen saturation measured by pulse oximeter.…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed that there was a significant enhancement in oxygen saturation evaluated by pulse oximeter. Also, a study made by Destanta et al 52 to investigate the impact of diaphragmatic deep breathing exercise on oxygen saturation in active smokers. The exercise resulted in significant improvement in oxygen saturation measured by pulse oximeter.…”
Section: Discussionmentioning
confidence: 99%